Using an RNA aptamer probe for flow cytometry detection of CD30-expressing lymphoma cells - Zhang, Peng (2009)
Aptamers are small molecular ligands composed of short oligonucleotides that bind targets with high affinity. In contrast to antibodies, as synthetic oligonucleotides, aptamers have lower production costs and elicit no antigenic reactions. Therefore, aptamers are potential agents for disease diagnosis and treatment. In this study, we validate a fluorescently labeled RNA aptamer, which has been reported to bind specifically to mouse CD30 proteins in solution, for human CD30 protein recognition on intact cells. The aptamer probe was tested with cultured anaplastic large cell lymphoma and Hodgkin′s lymphoma cells that express high levels of CD30. Flow cytometry and fluorescence microscopy showed specific and sensitive binding of the aptamer probe to CD30-expressing lymphoma cells at low concentrations (0.3 nM). Studies performed on multiple cell lines and nuclear cells from healthy donors confirmed that the CD30 aptamer and anti-CD30 antibody, the standard clinical probe, recognized the same set of cells. The potential application of multicolor flow cytometry analysis using the CD30 aptamer probe and antibodies was also shown. In conclusion, the developed CD30 aptamer probe could act as a replacement and/or a supplement for antibodies in the diagnosis of the CD30-expressing lymphomas.